ANALYSIS OF FINANCIAL PERFORMANCE BASED ON THE BALANCED SCORECARD METHOD BEFORE AND DURING COVID-19 PANDEMIC AT PT. BANK TABUNGAN NEGARA, TBK - Stenly Jacobus Ferdinandus; Reniati Reniati; Hillary Theophani Parera (Integrated Journal of Business and Economics (IJBE), 2022)
The balanced scorecard is a strategy implemented by the company in improving the overall performance of the company, which is not only seen from a financial perspective but also non-financial ones such as; customer perspective, internal business process perspective and learning and growth perspective. This study uses primary data in the form of a questionnaire and it is divided into two parts, namely before the COVID-19 pandemic and during the COVID-19 pandemic. The purpose of this study was to determine whether the balanced scorecard, in this case the four perspectives, had an effect on financial performance before the COVID-19 pandemic and during the COVID-19 pandemic at PT. Based on the results of research conducted, it can be seen that during the pandemic, the four perspectives of the balanced scorecard method, which are financial perspective, customer perspective, internal business process perspective, and growth and learning perspective, have a significant effect on financial performance. Meanwhile, during the COVID-19 pandemic, only financial perspective and growth and learning perspective have a significant effect on financial performance. However, the customer perspective and the internal business process perspective have no effect on financial performance.